Hard carbon material and preparation method and application thereof
By pre-oxidizing and carbonizing the polymer fiber material, hard carbon materials with excellent conductivity and performance stability were prepared, which solved the problems of low efficiency and unstable performance of traditional methods, and achieved efficient and low-cost hard carbon materials preparation.
Patent Information
- Application Number
- CN202411841774.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-29
AI Technical Summary
The preparation method of traditional hard carbon materials is low efficiency, high cost and unstable in performance, which limits its application in the battery field.
By pre-oxidizing and carbonizing the polymer fiber material, a hard carbon material with excellent conductivity and performance stability was prepared. The method includes vacuum drying, preoxidation, carbonization and refinement treatment, which improves the yield and performance of hard carbon materials.
It realizes efficient preparation of hard carbon materials, improves its conductivity and performance stability, and meets the needs of large-scale production and high-performance battery materials.
Smart Images

Figure CN119898746A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a hard carbon material and a preparation method and application thereof. Background Art
[0002] With the rapid development of electric vehicles, energy storage systems and other fields, the demand for high-performance battery materials is growing. Hard carbon materials have shown great application potential in the field of batteries, especially sodium-ion batteries, due to their high specific capacity and wide range of raw materials. However, the preparation methods of traditional hard carbon materials are inefficient and have problems such as unstable performance, which limits their promotion in practical applications.
[0003] Therefore, the present invention provides a new method for preparing hard carbon materials. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a hard carbon material and a preparation method and application thereof. The preparation method provided by the present invention has the advantages of high efficiency, low cost, simple operation, etc., and can significantly improve the performance stability of the prepared hard carbon material, and can meet the needs of large-scale production and high-performance battery materials.
[0005] In a first aspect, the present invention provides a method for preparing a hard carbon material, the preparation method comprising: pre-oxidizing a polymer fiber material, and then performing a carbonization treatment to obtain the hard carbon material.
[0006] The preparation method provided by the present invention has the advantages of high efficiency, low cost, simple operation, etc., and the prepared hard carbon material has excellent conductivity and performance stability, which can meet the needs of large-scale production and high-performance battery materials. Specifically:
[0007] The preparation method provided by the present invention first pre-oxidizes the polymer fiber material. On the one hand, it can reduce the content of oxygen-containing functional groups in the hard carbon product, reduce hard carbon defects, and thus reduce subsequent side reactions, thereby improving the conductivity, cycle performance and performance stability of the hard carbon material, etc., to meet the needs of high-performance battery materials; on the other hand, it can reduce carbon loss during the carbonization process, increase the hard carbon yield, improve the product economy, and the product batch stability is high, so that the preparation method of the present invention has the advantages of high efficiency, low cost, simple operation, etc., which meets the needs of large-scale production.
[0008] The hard carbon material yield η (%) = the mass of the obtained hard carbon material (m1) / the mass of the input polymer fiber material (m2)×100%.
[0009] As a preferred technical solution of the present invention, the polymer fiber material includes any one or more of dust-free paper, non-woven fabric and undyed fabric.
[0010] As a preferred technical solution of the present invention, the pre-oxidation is carried out in an air atmosphere.
[0011] As a preferred technical solution of the present invention, the pre-oxidation temperature is 180-250°C, for example, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, etc.
[0012] As a preferred technical solution of the present invention, the pre-oxidation time is 1-24h, for example, 1h, 2h, 4h, 8h, 12h, 16h, 20h, 24h, etc.
[0013] When the pre-oxidation temperature and time are within the above ranges, the prepared hard carbon material can have better conductivity and stability.
[0014] As a preferred technical solution of the present invention, the pre-oxidation temperature is 200-230°C.
[0015] As a preferred technical solution of the present invention, the pre-oxidation time is 1-3h.
[0016] When the pre-oxidation temperature and time are within the above ranges, the prepared hard carbon material can have better conductivity and stability.
[0017] As a preferred technical solution of the present invention, the carbonization treatment is carried out under an inert gas atmosphere, and the inert gas can be nitrogen, argon, etc.
[0018] As a preferred technical solution of the present invention, the heating rate of the carbonization treatment is 0.5-10°C / min, for example, 0.5°C / min, 1°C / min, 2°C / min, 5°C / min, 10°C / min, etc., preferably 1-5°C / min.
[0019] As a preferred technical solution of the present invention, the temperature of the carbonization treatment is 600-1700°C, for example, 600°C, 800°C, 1000°C, 1200°C, 1400°C, 1600°C, 17600°C, etc.
[0020] As a preferred technical solution of the present invention, the temperature of the carbonization treatment is 1000-1300°C.
[0021] As a preferred technical solution of the present invention, the carbonization treatment time is 1-10 hours, for example, 1 hour, 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, etc.
[0022] As a preferred technical solution of the present invention, the carbonization treatment time is 1-3h.
[0023] The present invention controls the temperature and time of the carbonization treatment within the above range to ensure that the dust-free paper is fully carbonized to obtain a high-performance hard carbon material.
[0024] The present invention does not impose too many restrictions on the equipment used for the carbonization treatment, as long as it can meet the requirements, for example, it can be a tubular furnace.
[0025] As a preferred technical solution of the present invention, the polymer fiber material is also subjected to vacuum drying treatment before pre-oxidation.
[0026] As a preferred technical solution of the present invention, the vacuum degree of the vacuum drying treatment is 0.1-100Kpa, for example, 0.1Kpa, 1Kpa, 5Kpa, 10Kpa, 50Kpa, 80Kpa, 100Kpa, etc.
[0027] As a preferred technical solution of the present invention, the temperature of the vacuum drying treatment is 105-120°C, for example, 105°C, 110°C, 115°C, 120°C, etc.
[0028] As a preferred technical solution of the present invention, the vacuum drying treatment time is 1-10 hours, for example, 1 hour, 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, etc.
[0029] As a preferred technical solution of the present invention, the water content of the polymer fiber material after vacuum drying is less than 500 ppm.
[0030] The present invention performs vacuum drying treatment on the polymer fiber material. When the treatment conditions are within the above range, the moisture in the material can be effectively removed to make its moisture content lower than a predetermined threshold, thus laying a good foundation for subsequent carbonization treatment.
[0031] As a preferred technical solution of the present invention, the carbonization treatment is followed by a refinement treatment.
[0032] As a preferred technical solution of the present invention, the method of the refining treatment is: ball-milling the hard carbon crude product obtained by carbonization treatment to obtain the hard carbon material.
[0033] As a preferred technical solution of the present invention, the ball milling is carried out using a planetary ball mill or a vibrating ball mill.
[0034] As a preferred technical solution of the present invention, the rotation speed of the ball mill is 100-500r / min, for example, 100r / min, 200r / min, 300r / min, 400r / min, 500r / min, etc.
[0035] As a preferred technical solution of the present invention, the ball milling time is 0.2-5h, for example, 0.2h, 1h, 2h, 3h, 4h, 5h, etc.
[0036] As a preferred technical solution of the present invention, the D50 of the hard carbon material obtained by the refinement treatment is 5-15 μm, for example, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, etc.
[0037] The present invention utilizes a ball mill to refine the hard carbon crude product to achieve a predetermined particle size distribution, thereby effectively improving its electrochemical performance.
[0038] As a preferred technical solution of the present invention, the method for preparing the hard carbon material comprises:
[0039] (1) vacuum drying the polymer fiber material to reduce the water content to less than 500 ppm, with a vacuum degree of 0.1-100 KPa, a temperature of 105-120° C., and a time of 1-10 h;
[0040] (2) pre-oxidizing the vacuum-dried polymer fiber material at a temperature of 180-250° C. for 1-24 h to obtain a hard carbon precursor;
[0041] (3) subjecting the hard carbon precursor to carbonization treatment at a temperature of 600-1700° C. for 1-10 h to obtain a hard carbon crude product;
[0042] (4) The hard carbon crude product is subjected to ball milling treatment at a rotation speed of 100-500 r / min and a time of 0.2-5 h to obtain the hard carbon material.
[0043] In a second aspect, the present invention provides a hard carbon material prepared by the preparation method described in the first aspect.
[0044] The hard carbon material prepared by the present invention has a 2 / g specific surface area and at least 200mAh / g reversible capacity. Compared with the hard carbon materials prepared by traditional methods, the first efficiency and cycle stability are greatly improved.
[0045] In a third aspect, the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the hard carbon material described in the second aspect.
[0046] As a preferred technical solution of the present invention, the negative electrode plate also includes a conductive agent and a binder.
[0047] As a preferred technical solution of the present invention, the conductive agent includes any one or more of carbon black, graphite and carbon nanotubes.
[0048] As a preferred technical solution of the present invention, the binder includes any one or more of styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC-Na), PAA, polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).
[0049] As a preferred technical solution of the present invention, the binder is selected from a combination of styrene-butadiene rubber and sodium carboxymethyl cellulose.
[0050] As a preferred technical solution of the present invention, in the negative electrode plate, the mass ratio of the hard carbon material, the conductive agent, sodium carboxymethyl cellulose and styrene-butadiene rubber is 90:(3-5):(2-4):(2-4).
[0051] In a fourth aspect, the present invention provides an electrochemical energy storage device, which includes the hard carbon material described in the second aspect or the negative electrode plate described in the third aspect.
[0052] As a preferred technical solution of the present invention, the electrochemical energy storage device is a sodium ion battery.
[0053] The sodium ion battery using the hard carbon material prepared by the present invention has a high first coulombic efficiency, excellent rate performance and cycle stability, etc., with a first coulombic efficiency of at least 86% and a cycle stability of at least 1,000 times. Compared with traditional negative electrode materials, its first coulombic efficiency is increased by 2-5%, and its cycle performance is increased by 20%, which can meet the needs of different application scenarios.
[0054] As a preferred technical solution of the present invention, the sodium ion battery comprises a positive electrode plate and a sodium salt electrolyte, and the sodium salt electrolyte is a liquid electrolyte or a solid electrolyte.
[0055] The technical solution provided by the embodiment of the present invention has the following advantages compared with the prior art:
[0056] The preparation method provided by the present invention has the advantages of high efficiency, low cost, simple operation, etc., and the prepared hard carbon material has excellent conductivity and performance stability, which can meet the needs of large-scale production and high-performance battery materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0058] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0059] Figure 1 This is the nitrogen adsorption-desorption curve of the hard carbon material prepared in Preparation Example 1 of the present invention;
[0060] Figure 2 This is the first charge and discharge curve of the sodium ion battery assembled with the negative electrode sheet prepared by the hard carbon material of Preparation Example 1 according to Example 1 of the present invention. DETAILED DESCRIPTION
[0061] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0062] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention can also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, not all of them. Unless otherwise specified, the raw materials are all commercially available.
[0063] Preparation Example 1
[0064] This preparation example provides a hard carbon material and a preparation method thereof, the preparation method comprising the following steps:
[0065] (1) 4 g of dust-free paper was vacuum dried at a vacuum degree of 0.1-20 KPa, a temperature of 105°C, and a time of 10 h;
[0066] (2) placing the vacuum-dried dust-free paper in a muffle furnace for pre-oxidation treatment at a temperature of 220° C. for 10 h to obtain a hard carbon precursor;
[0067] (3) transferring the hard carbon precursor to a tube furnace, heating the temperature to 1000°C at a heating rate of 2°C / min in an argon atmosphere (flow rate of 20 mL / min) for carbonization for 3 h to obtain a crude hard carbon product;
[0068] (4) The hard carbon crude product is placed in a ball mill for refining treatment at a rotation speed of 300 r / min for 3 hours until D50 is approximately 10 microns, thereby obtaining the hard carbon material.
[0069] Preparation Example 2-14
[0070] This preparation example provides a hard carbon material and a preparation method thereof. The preparation method is the same as Preparation Example 1. The difference from Preparation Example 1 is that the pre-oxidation temperature or carbonization temperature or heating rate is different, as shown in Table 1.
[0071] Preparation Example 15
[0072] This preparation example provides a hard carbon material and a preparation method thereof. The preparation method is the same as that of Preparation Example 1. The difference from Preparation Example 1 is that the dust-free paper is replaced by non-woven fabric in this preparation example.
[0073] Comparative Preparation Example 1
[0074] This comparative preparation example provides a hard carbon material and a preparation method thereof. The preparation method is the same as Preparation Example 1, and the difference from Preparation Example 1 is that the pre-oxidation treatment in step (2) is not performed in this comparative preparation example.
[0075] Comparative Preparation Example 2-3
[0076] This comparative preparation example provides a hard carbon material and a preparation method thereof. The preparation method is the same as Preparation Example 1. The difference from Preparation Example 1 is that the pre-oxidation treatment temperatures in this comparative preparation example are 150°C (Comparative Preparation Example 2) and 280°C (Comparative Preparation Example 3).
[0077] Comparative Preparation Example 4
[0078] This comparative preparation example provides a hard carbon material and a preparation method thereof. The preparation method is the same as Preparation Example 1, and the difference from Preparation Example 1 is that the temperature of the carbonization treatment in this comparative preparation example is 500°C (Comparative Preparation Example 4).
[0079] The preparation condition variables in each preparation example and comparative preparation example are shown in Table 1:
[0080] Table 1
[0081]
[0082]
[0083] Example 1
[0084] This embodiment provides a negative electrode plate and a preparation method thereof, wherein the hard carbon material is the hard carbon material prepared in Preparation Example 1, and the preparation method comprises:
[0085] Hard carbon material, conductive agent (Super P), sodium carboxymethyl cellulose and styrene-butadiene rubber were mixed in a mass ratio of 90:4:3:3, and negative electrode slurry was prepared with deionized water. The negative electrode slurry was then coated on aluminum foil with a coating thickness of 150 μm. It was then dried in an oven at 100°C for 2 h and cut with a cutter to obtain negative electrode sheets.
[0086] Example 2-15
[0087] This embodiment provides a negative electrode plate and a preparation method thereof. The preparation method is the same as that of Example 1. The difference from Example 1 is that in this embodiment, the hard carbon material is replaced by the hard carbon materials prepared in Preparation Examples 2-15 respectively.
[0088] Comparative Examples 1-4
[0089] This comparative example provides a negative electrode plate and a preparation method thereof. The preparation method is the same as that of Example 1. The difference from Example 1 is that in this comparative example, the hard carbon material is replaced by the hard carbon materials prepared in Comparative Preparation Examples 1-4 respectively.
[0090] Performance Testing
[0091] 1. Carry out nitrogen adsorption-desorption test on the prepared hard carbon material.
[0092] Among them, the nitrogen adsorption-desorption curve results of the hard carbon material obtained in Preparation Example 1 are as follows: Figure 1 It shows that the hard carbon material prepared by the present invention has fewer pores, higher density, fewer defects and excellent performance.
[0093] 2. Assembling sodium ion batteries using the negative electrode sheets prepared in the examples and comparative examples:
[0094] The negative electrode sheets prepared in the aforementioned embodiments and comparative examples were respectively used as the negative electrode sheets of the sodium ion battery, the metal sodium sheet was used as the positive electrode sheet, and the electrolyte was 1 mol / L NaPF6-EC / DMC (solvent EC:DMC=1:1, volume ratio), and CR2032 button batteries were assembled in a glove box.
[0095] Then the sodium ion battery was charged and discharged using the discharge procedure: 0.1C to 0V, standing for 10 minutes, 0.02C to 0V, and the charging procedure: 0.1C to 2.0V.
[0096] The results are shown in Table 2 and Figure 2 As shown, Figure 2 This is the first charge and discharge curve of the sodium ion battery assembled with the negative electrode sheet prepared by the hard carbon material of Preparation Example 1 in Example 1.
[0097] Table 2
[0098]
[0099]
[0100] From the comparison of the embodiments and the comparative examples, it can be found that the preparation method of the hard carbon material provided by the present invention has good reproducibility, high yield, and excellent conductivity and stability. When the hard carbon material prepared by the present invention is applied to sodium ion batteries, it has excellent rate performance and cycle performance, and high first coulombic efficiency, and has broad commercial application prospects.
[0101] From the comparison between Examples 1-2 and Examples 3-6 and 13, it can be found that when the carbonization temperature is higher or lower, the electrochemical performance decreases;
[0102] From the comparison between Examples 1-2, 12 and Examples 7-8, it can be found that when the pre-oxidation temperature is low, the electrochemical performance decreases;
[0103] From the comparison between Examples 1-2, 14 and Example 9, it can be found that when the carbonization time is longer, the electrochemical performance decreases;
[0104] From the comparison between Examples 1-2 and Examples 10-11, it can be found that when the heating rate is faster, the electrochemical performance decreases.
[0105] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0106] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments described herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a hard carbon material, characterized in that: The preparation method comprises: pre-oxidizing the polymer fiber material and then performing a carbonization treatment to obtain the hard carbon material.
2. The preparation method according to claim 1, characterized in that: The polymer fiber material includes any one or more of dust-free paper, non-woven fabric and undyed fabric.
3. The preparation method according to claim 1 or 2, characterized in that: The pre-oxidation temperature is 180-250°C; And / or, the pre-oxidation time is 1-24h.
4. The preparation method according to claim 1 or 2, characterized in that: The carbonization treatment is carried out under an inert gas atmosphere; And / or, the heating rate of the carbonization treatment is 0.5-10°C / min; And / or, the temperature of the carbonization treatment is 600-1700°C; And / or, the carbonization treatment time is 1-10 hours.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The polymer fiber material is also subjected to vacuum drying treatment before pre-oxidation; Preferably, the vacuum degree of the vacuum drying process is 0.1-100 KPa; Preferably, the temperature of the vacuum drying treatment is 105-120°C; Preferably, the vacuum drying treatment time is 1-10h; Preferably, the water content of the polymer fiber material after vacuum drying is less than 500 ppm.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The carbonization treatment is followed by a refinement treatment; Preferably, the refinement method is: ball-milling the hard carbon crude product obtained by carbonization to obtain the hard carbon material.
7. The preparation method according to claim 6, characterized in that: The rotation speed of the ball mill is 100-500r / min; And / or, the ball milling time is 0.2-5h.
8. The hard carbon material prepared by the preparation method according to any one of claims 1 to 7.
9. A negative electrode plate, characterized in that: The negative electrode plate comprises the hard carbon material according to claim 8.
10. An electrochemical energy storage device, characterized in that: The electrochemical energy storage device comprises the hard carbon material according to claim 8 or the negative electrode sheet according to claim 9.
Citation Information
Patent Citations
Flexible electrode material as well as preparation method and application thereof
CN107275577A
High-capacitance lithium battery carbon negative electrode material as well as preparation method and application thereof
CN111864203A
Selenium-containing compound / carbon fiber energy storage material as well as preparation method and application thereof
CN114023957A
Preparation method of sodium ion battery hard carbon-based negative electrode material based on waste fabric recycling
CN116705999A
Self-supporting biomass carbon negative electrode material and preparation method thereof
CN118419906A